ANALISIS BEBAN KERJA MENGGUNAKAN HIRARC PADA DAPUR TDHT PHASE-1 PT. ARYA WIRA DINAMIKA - Arya Fahrezi, Arief; Yamani, Achmad Zaki; Qurthuby, Muhammad (Fakultas Teknik UMRI, 2022)
At PT. Arya Wira Dinamika is a contracting company engaged in mining & construction contracts. This research is for the Retubing Furnance work 018F-102 Green Refinery Revamp TDHT PHASE-1 in the FOC-2 Pertamina RU IV Area because the work place is at a height and has limited activity space in the oil processing kitchen, the risk of hazard is fairly high. This study was conducted to analyze occupational risks using the HIRARC (Hazard Identification, Risk Assessment, & Risk Control) method. Based on the analyzed data, it was found that there are 10 risks of work accidents in the work process of Retubing Furnance 018F-102 Green Refinery Revamp, there is 1 type of activity that is categorized as small risk, 5 types of activity with moderate risk category, and 4 types of risk with high category. From the results of the HIRARC analysis and assessment, workers are required to use PPE (Personal Protective Equipment) in accordance with the regulations from the company and from Pertamina RU IV and the type of work carried out and must comply with the SOPs applicable to the company.